Behavior of RC Wide Beams under Eccentric Loading - Samer Magdy Mahmoud; Rasha T. S. Mabrouk; Magdy E. Kassem (Civil Engineering Journal, 2021)
Wide beams are one of the widely used structural elements in RC buildings due to the many special features that characterize them. The main objective of this research is to investigate the behavior of wide shallow beams under the effect of eccentric loading acting along their cross sections. To achieve that, an experimental program that consisted of seven wide beams was conducted. All beams were loaded using two concentrated loads at their middle third where the main parameters considered were: the magnitude of the load eccentricity, the longitudinal spacing between shear reinforcement, and the arrangement of the longitudinal reinforcement. Following that, a finite element analysis was performed where the analytical model used was first verified using the data from the experimental program. The results from both the experimental and analytical programs were in good agreement. Then, the finite element analysis was extended through a parametric study where other variables were studies such as the compressive strength of concrete, the transverse spacing between stirrups and the longitudinal reinforcement ratio. The results showed that the value of the load eccentricity, spacing between shear reinforcement, the arrangement of the main reinforcement along the beam cross section, and the compressive strength of concrete significantly affected the torsional resistance of shallow wide beams. Conclusions and recommendations are presented which can be useful for future researchers. Doi: 10.28991/cej-2021-03091766 Full Text: PDF